Ecological Analysis of Post-Mining Bauxite Void Waters in Bintan Regency Based on Water Quality Parameters - Reza Muzzamil Jufri; Maryono Maryono; Fuad Muhammad (Eduvest - Journal of Universal Studies, 2025)
Bauxite mining that has been ongoing for decades in Bintan Regency, Riau Islands Province, has left several voids or former excavated ponds. The existence of these post-mining voids has the potential to affect environmental quality, especially regarding water quality components and the suitability of land use in the surrounding area. This study aims to analyze the current condition of bauxite void water quality after mining in Bintan Regency as a basis for assessing the ecological aspects of the post-mining area. The analysis was conducted descriptively and comparatively by comparing the physico-chemical water parameters against class II water quality standards, in accordance with Government Regulation Number 22 of 2021. Data were obtained from the Bintan Regency Environment Agency (DLH) in 2023, including parameters such as pH, DO, BOD, COD, TSS, TDS, Total Phosphate, and Fecal Coliform. The results showed that most of the water quality parameters were within the class II standard range, except for pH, which varied between 0.24 and 7.75, indicating that some locations were highly acidic. The pH value is the main limiting parameter in determining the ecological conditions of the post-mining voids. Based on the calculation of the compliance score, about 68.8% of voids are classified as "Appropriate," and 31.2% as "Fairly Appropriate." These findings indicate that most voids have undergone natural stabilization processes, although some still require advanced ecological rehabilitation to normalize water quality and support post-mining environmental functions.